2005
DOI: 10.1213/01.ane.0000152324.30272.49
|View full text |Cite
|
Sign up to set email alerts
|

The NR3B Subunit Does Not Alter the Anesthetic Sensitivities of Recombinant N-Methyl-d-Aspartate Receptors

Abstract: The N-methyl-D-aspartate (NMDA) receptor NR3B subunit co-assembles with NR1 and NR2 subunits to form a receptor complex with distinct channel properties. In the present study, we investigated the effects of co-expression of the NR3B subunit on the anesthetic sensitivities of NMDA receptors for NR1/NR2 channels expressed in Xenopus oocytes. Although the NR3B subunit prominently reduced the current amplitude of NR1/NR2A-B channels, the sensitivities of NR1/NR2A-B channels to Mg2+, ketamine, isoflurane, nitrous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Increasing the amount of NR3B cDNA with respect to NR1 and NR2A correspondingly reduced the current amplitudes (Nishi et al, 2001). This is consistent with that reported in X. laevis oocyte expression system (Yamakura et al, 2005) that NR3 subunits exert a negative interfering effect in NMDA receptors Sucher et al, 1995;Das et al, 1998;Chatterton et al, 2002;Matsuda et al, 2002Matsuda et al, , 2003Yamakura et al, 2005).…”
Section: Nr1/nr3 Receptors Expressed In Oocytessupporting
confidence: 90%
See 2 more Smart Citations
“…Increasing the amount of NR3B cDNA with respect to NR1 and NR2A correspondingly reduced the current amplitudes (Nishi et al, 2001). This is consistent with that reported in X. laevis oocyte expression system (Yamakura et al, 2005) that NR3 subunits exert a negative interfering effect in NMDA receptors Sucher et al, 1995;Das et al, 1998;Chatterton et al, 2002;Matsuda et al, 2002Matsuda et al, , 2003Yamakura et al, 2005).…”
Section: Nr1/nr3 Receptors Expressed In Oocytessupporting
confidence: 90%
“…The cotransfection of NR1, NR3A, and NR3B cDNAs into HEK293 cells produces triheteromeric NR1/NR3A/NR3B receptors yielding glycine-activated currents with novel functional and pharmacological properties (Pina-Crespo and Heinemann, 2004;Smothers and Woodward, 2007;Talantova et al, 2007). The glycine-activated currents of NR1/NR3A/ NR3B receptors resemble that observed in oocytes expressing NR1/NR3A (i.e., currents undergo rapid activation followed by rapid desensitization to steady-state levels) (Chatterton et al, 2002;Yamakura et al, 2005). The desensitization of activated NR1/NR3A/NR3B receptors is not affected by cyclothiazide.…”
Section: Nr1/nr3 Receptors Expressed In Oocytesmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, another study showed that the sensitivities of NMDA receptors to Mg 2ϩ , isoflurane, ketamine, nitrous oxide, and ethanol were not altered by the NR3B subunit, although the NR3B subunit prominently reduced the amplitude of NMDA currents. 44 These results indicate that NMDA receptor-mediated synaptic transmission may not be affected by xenon in adult motoneurons. In any case, additional studies are required using identified spinal motoneurons in the adult rat.…”
Section: Discussionmentioning
confidence: 81%
“…Ketamine blocks NMDA receptors through an interaction with sites thought to be located within the ion channel pore region (Orser et al, 1997). Recently, it was shown that inclusion of the NR3B subunit does not alter the ketamine sensitivity of recombinant NR1/NR2 receptors expressed in oo- jpet.aspetjournals.org cytes (Yamakura et al, 2005), Likewise, 100 M ketamine produced only weak inhibition (4.3 Ϯ 3.3% peak component and 7.9 Ϯ 6.8% steady-state component) of the glycineinduced current of NR1/NR3A/NR3B receptors (Fig. 9, B and C).…”
Section: Resultsmentioning
confidence: 99%